1989
DOI: 10.1073/pnas.86.10.3509
|View full text |Cite
|
Sign up to set email alerts
|

Infectious in vitro transcripts from cloned cDNA of a potyvirus, tobacco vein mottling virus.

Abstract: Full-length cDNA copies of tobacco vein mottling virus (TVMV) RNA were constructed downstream from bacteriophage T7 or T3 RNA polymerase promoters. The plasmids were designed to produce in vitro transcripts containing, respectively, one or two guanosine residues at the 5' terminus not derived from the TVMV sequence and a single cytidine residue at the 3' terminus following the poly(A)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
1

Year Published

1990
1990
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(40 citation statements)
references
References 33 publications
1
38
1
Order By: Relevance
“…Also the high stability of satRNA (Murant & Raschk6, 1982) could have a similar effect. Unlike the results obtained with transcripts of other naturally non-capped virus RNAs (Vos et al, 1988;Domier et al, 1989) capping of the 5' terminus of the synthetic satRNA transcripts had no detectable effect on their multiplication. It remains to be demonstrated whether the addition of VPg occurred, and favoured further replication of the progeny RNA.…”
Section: Discussioncontrasting
confidence: 91%
“…Also the high stability of satRNA (Murant & Raschk6, 1982) could have a similar effect. Unlike the results obtained with transcripts of other naturally non-capped virus RNAs (Vos et al, 1988;Domier et al, 1989) capping of the 5' terminus of the synthetic satRNA transcripts had no detectable effect on their multiplication. It remains to be demonstrated whether the addition of VPg occurred, and favoured further replication of the progeny RNA.…”
Section: Discussioncontrasting
confidence: 91%
“…cDNAs representing the P1 and P3 coding regions of TVMV RNA were generated using synthetic oligonucleotides as primers for PCR in which the template was the full-length infectious clone pXBS7 (Domier et al, 1989). The P1 coding region was amplified with oligonucleotides A and B and the P3 region with oligonucleotides C and D described in Rodrı!…”
Section: Methodsmentioning
confidence: 99%
“…Nucleic acids (5 µg) were transferred to Hybond membranes (Amersham) by the capillary blot procedure. Transgene-derived P3 RNA was detected with a $#P-labelled complementary RNA (cRNA) probe prepared by in vitro transcription of a subclone of pXBS7 (Domier et al, 1989) containing a 758 bp HindIII fragment (residues 2093-2851 of TVMV RNA). For detecting P1 transgene-derived RNAs in Northern blots, a fragment of pXSB7 was amplified by PCR with oligonucleotides A and B (Rodrı!…”
Section: Inoculation and Evaluation Of Transgenic Plants Seedlingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The delayed appearance of lesions on leaves inoculated with the original transcripts suggested that some of the clones had in vivo repairable defects. The length of 3-terminal A residues of our clones ranged from 24 to 28, and previous work has documented that increasing the length of the poly (A) tail could increase infectivity of viral cDNA transcripts [13,15,16,35,45]. This possibility was tested by selecting the three of the original 19 plasmids that gave delayed infectivity, plus two others that appeared to be noninfectious, for polyadenylation studies.…”
Section: Infectious Transcripts From In Vitro Transcribed Fomv Cdnamentioning
confidence: 99%